CLINICAL CHARACTERISTICS AND EFFICACY OF PHOTOTHERAPY FOR NEONATAL UNCONJUGATED HYPERBILIRUBINEMIA AT PHU THO OBSTETRICS AND PEDIATRICS HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: evaluation of the clinical characteristics, etiologies, and efficacy of phototherapy for neonatal unconjugated hyperbilirubinemia at Phu Tho Obstetrics and Pediatrics Hospital from January 2026 to April 2026.Research objects and methods: A cross-sectional descriptive study was conducted on 139 neonates diagnosed with unconjugated hyperbilirubinemia who met the criteria for phototherapy according to the NICE 2010 guidelines, from January to April 2026.Results: The study population showed a male predominance, with a male-to-female ratio of 1.72:1. Jaundice developed after 48 hours of age in 66.19% of neonates and Kramer score 4 was the most common clinical presentation. ABO incompatibility represented the leading identified pathological etiology, accounting for 14.4% of cases. Exclusive breastfeeding was associated with a significantly greater decline in serum bilirubin concentrations and a shorter phototherapy duration than formula feeding or mixed feeding (p < 0.05). Phototherapy achieved a 100% treatment success rate, and no infant required exchange transfusion.Conclusion: Phototherapy was the main treatment used in this study and showed good results in the infants who were followed up. Early screening for ABO incompatibility and maternal-fetal risk factors is recommended to optimize management.
Keywords: Neonatal jaundice; Phototherapy; Hyperbilirubinemia.